Woody species diversity, productivity and carbon stock potential of dry deciduous woodland in Alitash National Park, North West Ethiopia - Andargie, Amsalu Abich; Abtew, Asmamaw Alemu; Azagew, Tadesse Mucheye; Asres, Mequanent Tebikew; grima, Yohannis Gebremariam (International Journal of Scientific Research and Management (IJSRM), 2018)
Dry woodlands provide multifunctional benefits which grouped socioeconomic and ecological values. Despite these advantageous while recently threatened, the status of dry woodland attribute is not well understood, particularly Alitash National Park (ANP). Hence, woody species diversity, productivity and carbon stock potential of ANP were studied. Based on the collected data, a total of 24 woody species were identified. The computed Shannon-Wiener's diversity and evenness index were 2.11 and 0.66, respectively which indicated that moderate diversity and individual species were sparsely distributed horizontally. The study site was dominated by few individuals of woody species that exhibited the highest value of IVI. Population structure pattern of woody species showed F shape indicates the first class exhibited good regeneration. Whereas, species in the second classes interrupted the seedling establishment phase and transformation to sapling stage as a result of disturbance caused by anthropogenic, grazing and frequent firing. Stand basal area, volume and AGB were 8.57 m2ha-1, 48.15 m3ha-1 and 49.06 ton ha-1, respectively. The estimated carbon stock of the stand was 27.7 ton ha-1. In conclusion, the results of woody vegetation attributes showed ANP is affected negatively caused by different disturbance indicate the need of appropriate intervention and management system although ANP is protected.